The FDA “Black Box” Warning on Antidepressant Suicide Risk in Young Adults: More Harm Than Benefits? - Fornaro, Michele; Anastasia, Annalisa; Valchera, Alessandro; Carano, Alessandro; Orsolini, Laura; Vellante, Federica; Rapini, Gabriella; Olivieri, Luigi; Di Natale, Serena; Perna, Giampaolo; Martinotti, Giovanni; Di Giannantonio, Massimo; et al. (Frontiers in Psychiatry, 2019)
The U.S. Food and Drug Administration (FDA) “, black box” warning on antidepressant suicide in young people grounds on industry-sponsored trials, often carried over a decade ago. Within the past decade, an increasing number of reports questioned the actual validity of the FDA warning, especially considering that increased suicidal events parallelled the decline in antidepressant drug prescription for severe depression. The present report provides an overview of the FDA “black box” warning, also documenting two Major Depressive Disorder patients whose refusal to undergo a pharmacological antidepressant treatment most likely affected the outcome of depression, the onset of suicidal behavior, possibly due to the stigma against the antidepressant drugs. As critically appraised in the text, the potentially detrimental consequences of the concerns raised by the FDA “black box” label warning need to be considered in the real-world clinical practice, stating the associated clinical and public health implications.